GEOLOGI DAN PEMODELAN RESERVOIR FORMASI TAWUN PADA LAPANGAN KMN, CEKUNGAN JAWA TIMUR UTARA - Jasmine, Marisa
Administratively, KMN Field is located in Central Java Province which is encompassing an area about 17.50 km2. Geologically, KMN Field is located in Rembang zone at West Cepu High, southwest-northeast oriented anticline that is located in North East Java Basin. The study is focusing in Tawun Formation with three reservoir intervals which are Reservoir M0, Reservoir FS2, and Reservoir Intra Tawun, and sandstone as its lithology. The main purposes of this study are to determine the reservoir model and to estimate the original oil in place (OOIP) as well as original gas in place (OGIP) of those three reservoirs in KMN Field. The data used in this study are wireline log and cutting from 4 wells, 2D seismic data, and sidewall core data from 3 wells. Several methods have been performed in order to achieve those main purposes which are; first is well data analysis which is using sequence stratigraphy concept to correlate the well, then electrofacies analysis from log data and cuttings, and also petrophysic analysis. Second is seismic data analysis to generate the depth structure map. Third is reservoir modelling which consists of determination of three dimensional structure model, petrophysic property modelling, fluid contact, and estimation original hydrocarbon in place (OOIP and OGIP). The result by implementing those methods are, main structural geology in KMN Field are relative west-east trending anticline, associate with thrust faults in the same direction. Reservoir M0 is described as Foreshore Carbonate, Foreshore Sand and Shoreface Sand. Reservoir FS2 also has the typical deposits as Reservoir M0. While Reservoir Intra Tawun is described as Transgressive Shelf Sand, with the same sedimentation path which is nortwest-southeast. The estimation of original hydrocarbon in place (OOIP and OGIP) in three reservoir intervals are 5,8 million STB for OOIP and 7,3 million MSCF for OGIP.